2008
DOI: 10.1007/978-3-540-88690-7_24
|View full text |Cite
|
Sign up to set email alerts
|

A New Baseline for Image Annotation

Abstract: Abstract. Automatically assigning keywords to images is of great interest as it allows one to index, retrieve, and understand large collections of image data. Many techniques have been proposed for image annotation in the last decade that give reasonable performance on standard datasets. However, most of these works fail to compare their methods with simple baseline techniques to justify the need for complex models and subsequent training. In this work, we introduce a new baseline technique for image annotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
382
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 346 publications
(391 citation statements)
references
References 19 publications
(21 reference statements)
7
382
2
Order By: Relevance
“…More recently Makadia et al [28] have proposed a new, simple set of baseline image features for image annotation problems. They also proposed a simple technique to combine distance computations to create a nearest neighbor classifier suitable for baseline experiments.…”
Section: Image Features For Annotationmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently Makadia et al [28] have proposed a new, simple set of baseline image features for image annotation problems. They also proposed a simple technique to combine distance computations to create a nearest neighbor classifier suitable for baseline experiments.…”
Section: Image Features For Annotationmentioning
confidence: 99%
“…In a comparison of four distance measures (KL-divergence, a χ 2 statistic, L 1 -distance, and L 2 -distance) on the Corel dataset, [28] found that L 1 performed the best for RGB and HSV while the KL-divergence was better suited for LAB.…”
Section: Image Features For Annotationmentioning
confidence: 99%
See 3 more Smart Citations